Development of an acute medical unit to optimize patient flow and early discharges in a tertiary care hospital in the United Arab Emirates - Thana Harhara; Halah Ibrahim; Waqar H. Gaba; Ashraf M. Kamour (BMC, 2022)
Abstract Background Hospitals worldwide are seeing an increased number of acute admissions, with resultant emergency department (ED) crowding and increased length of stay (LOS). Acute Medical Units (AMUs) have developed throughout the United Kingdom and other Western countries to reduce the burden on EDs and improve patient flow. Limited information is available on AMUs in the Middle East. The purpose of this study is to describe the development of the first AMU in the United Arab Emirates (UAE) for general medical patients and its impact on LOS, early discharges, ED boarders, and readmission rates. Methods We established a consultant-led AMU in a tertiary hospital in the UAE. A retrospective comparative review of all general medical admissions to the AMU between August 1, 2020 and December 31, 2020 and all admissions to the traditional medical wards between August 1, 2019 and December 31, 2019 was conducted. Results The average LOS reduced from 10 to 5 days (95% CI [4.14-6.25], p < 0.001) after the introduction of AMU. Early discharges increased by 22%. The number of outliers and number of patients boarding in ED reduced significantly (111 in 2019 vs. 60 in 2020, p < 0.05; 938 in 2019 vs. 104 in 2020, p < 0.001 respectively), with a decrease in ED waiting time from 394 min to 134 min (95% CI [229.25-290.75], p < 0.001). There was no increase in 30-day readmission rates. Conclusion Restructuring the system of care can reduce LOS, overcome discharge barriers and improve patient flow. Similar units can be developed in hospitals throughout the UAE and the region to reduce LOS and improve patient flow through acute care units.